Political, Economic, Historical, Social and Spiritual Life during the Reign of Amir Temur - Kholmamatovna, Jabborova Qizlargul (Research Parks Publishers, 2022)
The article examines the spiritual heritage left by our ancestors, in particular, the wonderful progressive ideas of Amir Temur, necessary for all spheres and for all periods.